The Pathway of Adopting Omnibus Law in Indonesia's Legislation: Challenges and Opportunities in Legal Reform - Sulistina Sulistina; Bayu Dwi Anggono; Al Khanif; Tran Ngoc Dinh (University of Jember, Indonesia, 2022)
The omnibus law model has become a new method of legislative drafting in Indonesia, first applied to the Job Creation Law and later enacted as Law 11/2020. While there were no implicit guidelines in Legislative Drafting Law 12/2011, this adoption was imported from several countries like the United States and Ireland to simplify regulations before the method was subsequently formalized and included in Legislative Drafting Law 13/2022. This paper explored the pathway and dynamics of the omnibus law adoption in Indonesia's law-making procedure and analyzed its further impacts on whether such a method has fruitfully improved the quality of the enacted regulation in establishing a more friendly investment policy. Through doctrinal method, this study showed that the opportunity to apply the omnibus model in Indonesia depends on the effectiveness, success, and benefits of respective regulations. In contrast, the application of the omnibus law model should respect democratic principles and avoid public harm. As shown in three different countries, i.e., Indonesia, the United States, and Canada, public concerns on lack of participation should be taken seriously to hinder undemocratic ends through